Potential Piperolactam A Isolated From Piper betle as Natural Inhibitors of Brucella Species Aminoacyl‐tRNA Synthetase for Livestock Infections: In Silico Approach - Diding Latipudin; Sefren Geiner Tumilaar; Yoga Ramdani; Dudi Dudi; Dikdik Kurnia (Veterinary Medicine and Science)
ABSTRACT Brucellosis is an important global zoonosis caused by the bacterium Brucella sp. Brucellosis causes abortions, reproductive failure and reduced milk production, resulting in significant economic losses. Brucella species are reported to be resistant to antibiotics, which makes treatment difficult. The urgency of discovering new drug candidates to combat Brucella’s infection necessitates the exploration of novel alternative agents with unique protein targets. Aminoacyl‐tRNA synthetases (aaRSs), which have fundamental functions in translation, inhibit this process, stop protein synthesis and ultimately inhibit bacterial growth. The purpose of this study was to isolate piperolactam A compounds from the methanol extract of Piper betle leaves that have potential as antibacterials to inhibit the growth of Brucella sp. causing brucellosis in livestock and to analyse the mechanism of inhibitory activity of piperolactam A compounds against the aaRS enzyme through a molecular docking approach in silico. Piperolactam A was isolated from P. betle by column chromatography and characterized by UV, IR, 1D and 2D NMRs and MS, then tested for their inhibition mechanism against the enzymes threonyl‐tRNA synthetase, leucyl‐tRNA synthetase (LeuRS) and methionyl‐tRNA synthetase in silico. The result in silico test is that piperolactam A has the potential to inhibit LeuRS enzyme with the greater binding affinity.